2022
DOI: 10.1111/cea.14179
|View full text |Cite
|
Sign up to set email alerts
|

Detection and management of milk allergy: Delphi consensus study

Abstract: Background: There is significant overdiagnosis of milk allergy in young children in some countries, leading to unnecessary use of specialized formula. This guidance, developed by experts without commercial ties to the formula industry, aims to reduce milk allergy overdiagnosis and support carers of children with suspected milk allergy. Methods: Delphi study involving two rounds of anonymous consensus building and anopen meeting between January and July 2021. Seventeen experts in general practice, nutrition, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…Our data do not allow us to link purchases to infant diagnoses but does align with other studies that have shown that CMPA in infants is likely over‐diagnosed 41 due to guidelines that label potentially normal infant symptoms as a possible milk allergy 42–45 . In fact, an independent expert consensus recently suggested that narrower criteria are needed to diagnose milk CMPA to avoid unnecessary use of hypoallergenic formula 46 . Unnecessary use of a hypoallergenic formula in the US is additionally concerning as it also means consumption of lactose‐free formula and is more expensive for the consumer.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Our data do not allow us to link purchases to infant diagnoses but does align with other studies that have shown that CMPA in infants is likely over‐diagnosed 41 due to guidelines that label potentially normal infant symptoms as a possible milk allergy 42–45 . In fact, an independent expert consensus recently suggested that narrower criteria are needed to diagnose milk CMPA to avoid unnecessary use of hypoallergenic formula 46 . Unnecessary use of a hypoallergenic formula in the US is additionally concerning as it also means consumption of lactose‐free formula and is more expensive for the consumer.…”
Section: Discussionsupporting
confidence: 59%
“…[42][43][44][45] In fact, an independent expert consensus recently suggested that narrower criteria are needed to diagnose milk CMPA to avoid unnecessary use of hypoallergenic formula. 46 Unnecessary use of a hypoallergenic formula in the US is additionally concerning as it also means consumption of lactose-free formula and is more expensive for the consumer.…”
Section: 5% Hypoallergenicmentioning
confidence: 99%
“…When breastmilk is not available or insufficient an extensively hydrolysed formula (EHF) is the first‐choice formula for mild‐to‐moderate CMA and an aminoacidic formula (AAF) if EHF fails 33–38 . Restrictive criteria for milk allergy diagnosis have been proposed in order to avoid overdiagnosis and excessive use of milk formula substitutes 16,39,40 …”
Section: Management Optionsmentioning
confidence: 99%
“…In this issue, Allen et al present new milk allergy guidance. 6 They evaluated whether a non-conflicted, multidisciplinary panel of experts informed by patient perspectives might come to different conclusions, compared with milk allergy guidelines associated with formula industry conflicts. They found that guidance produced without formula industry conflicts leads to narrower criteria for detecting milk allergy, more explicit support for breastfeeding women in the context of milk allergy diagnosis, and more restrictive indications for specialized formula use.…”
Section: Clinical and Experimental Allergy Boycotts Formula Advertisingmentioning
confidence: 99%
“…Milk allergy guidelines are often supported or disseminated by the formula industry and usually written by experts who have received funding from the formula industry. In this issue, Allen et al present new milk allergy guidance 6 . They evaluated whether a non‐conflicted, multidisciplinary panel of experts informed by patient perspectives might come to different conclusions, compared with milk allergy guidelines associated with formula industry conflicts.…”
Section: Figurementioning
confidence: 99%